Sistem Informasi SDN Paron 02 Berbasis Web - Sulistyana, Andreas Rendiana; Utomo, Pradityo (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
The Internet is one of the development of information technology. In this case, there are many information systems that use the internet. Information systems created using the internet are called websites. In a study conducted at Paron State Elementary School 02 will be built a web-based school information system.School information systems can help Paron State Elementary School 02 to promote information teaching and learning process in the field of education. Information system Paron 02 State Elementary School web-based this will be built using waterfall method. Waterfall method is very complex and most suitable if applied to the information system that I created. The Paron 02 State Elementary Information System is built on a web-based basis. Where the system can be accessed online by the user. So the system has been built will run according to the function and the desired destination Paron State Elementary School 02. Users can find information in Paron 02 State Elementary School just by using the internet, users do not need to come to school to get information.Â Keywords : SDN Paron 02 Promotion, Information System, waterfall.